Reign Direct Investment and the Romanian Economy - Elena Chirila Donciu (CES Working Papers, 2015)
In a country's economy, investments take center stage, both in the production of goods and services and in the sphere of consumption. They represent a factor that influences simultaneously both demand and supply. The importance and impact of FDI have righteously attracted all EU Members heed and resulted in a fierce competition for foreign capital. The purpose of this paper is to analyze the impact of FDI on Romania economic growth. Research results show that FDI have a positive impact through the medium of productivity and competitiveness growth in the host countries, by means of technology and capital transfer.
Keywords: E22; F14; F43; 330; foreign direct investment; growth economy